Caracterización de modelos no-lineales casi-estáticos a partir de las formas de onda en régimen de gran señal - Pérez-Parras, Sergio Luis; Martín-Guerrero, Teresa María; Baños-Polglase, Juana Daphne; Camacho-Peñalosa, Carlos (My University, 2018)
A method to extract the conduction and displacement components of nonlinear quasi-static current sources controlled by two variables is concisely described. The method is numerically tested by means of two different analytical examples of nonlinear current sources. The obtained results clearly illustrate its performance as well as its potentiality in the nonlinear modelling of FET/HEMT devices
Keywords: Radio - Congresos; Modelos No-lineales; Modelos casi-estáticos; Modelos FET